The Role of Islamic Higher Education in Developing Human Resources for the Global Halal Industry: Synchronizing Curriculum - Wafiyah, Ummul (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The worldwide halal business is growing exponentially, yet Islamic Higher Education Institutions (PTI) graduates lack the skills needed to handle sharia, science, and halal. Current courses typically overemphasize normative knowledge without appropriately integrating global industrial standards, accreditation, and technology. This study examines PTI's strategic role in growing global halal sector human resources and develops a curriculum synchronization model to meet market expectations in halal assurance systems, Islamic finance, and halal tourism. This study uses a descriptive qualitative method with a case study approach at several leading PTI with halal-related study programs. Data were collected through analysis of curriculum documents (syllabus, RPS), in-depth interviews with stakeholders (academics, halal industry practitioners, and the Halal Product Assurance Agency/BPJPH), and FGDs (focus group discussions) for data triangulation. The results of the study indicate that effective curriculum synchronization requires modification of three main pillars: (1) integration of professional certification courses (such as Halal Slaughterer and Halal Auditor) into the compulsory curriculum, (2) increasing the portion of internships and project-based Field Work Practices (PKL) in global halal-certified companies, and (3) implementation of the